Case Study: Treatment of Autis Children - Ade Tursina; Veryawan Veryawan (SELING: Jurnal Program Studi PGRA, 2022)
This research is focused on providing an overview of new knowledge on how to handle children with autism who are in Early Childhood Education institutions. In the Pembina State Kindergarten, Langsa City has early childhood children who have autism and are in the same learning class with other normal children. The research aims to describe (1) the characteristics of autistic children in the Pembina State Kindergarten of Langsa City, (2) the teacher's way of dealing with autistic children in the Pembina State Kindergarten of Langsa City. (3) knowing the obstacles faced by teachers in dealing with autistic children in the Pembina State Kindergarten of Langsa City. This study uses a qualitative approach and the type of case study research in class B2 the Pembina State Kindergarten of Langsa City. Data collection techniques used are observation, interviews, and documentation. The results of this study indicate that (1) the characteristics of autistic children are hyperactive, like to be alone, have unstable emotions, avoid eye contact with other people, and do not want to communicate with the surrounding environment. (2) the handling carried out by the the Pembina State Kindergarten of Langsa City teachers for autistic children by giving special attention, giving hugs, stroking their heads and embracing them so that children want to play while learning activities. (3) the obstacles experienced in handling autistic children include: The absence of special teachers to handle children with special needs in the TK Negeri Pembina Kota Langsa.